Towards Innovative Ways to Assess Annoyance - Lavandier, C.; Aalmoes, R.; Dedieu, R.; Marki, F.; Grossarth, S.; Schreckenberg, D.; Gharbi, A.; Kotzinos, D. (Springer, 2022)
Technological changes have driven the developments in the field of noise annoyance research. It helped to increase knowledge on the topic substantially. It also provides opportunities to conduct novel research. The introduction of the internet, the mobile phone, and miniaturisation and improved sensor technology are at the core of the three research examples presented in this chapter. The first example is the use of a Virtual Reality simulation to evaluate aircraft flyovers in different environments, and it examines how visual perception influences noise annoyance. The second example describes the use of a mobile application applying an Experience Sampling Method to assess noise annoyance for a group of people living near an airport. The third and final example is a study over social media discussions in relation to noise annoyance and quality of life around airports. These three examples demonstrate how novel technologies help to collect and analyse data from people who live around airports, and so improve our understanding of the effect of noise on humans.